1992
DOI: 10.1254/jjp.60.403
|View full text |Cite
|
Sign up to set email alerts
|

KCl-Depolarization Potentiates the Ca2+Sensitization by Endothelin-1 in Canine Coronary Artery

Abstract: ABSTRACT-In Ca2-free solution containing endothelin-1 (ET-1), depolarization by high KCl in creased the force of contraction without any changes in intracellular calcium concentration ([Ca 2+]i) in canine coronary artery. The [Ca 2+];-force relationships were examined in the absence or presence of ET-1 in 5 or 90 mM KCI. The relation curve in the presence of ET-1 in 90 mM KCl-PSS was shifted to the left and upward compared with that in 5 mM KCI. These results suggest that KCl-depolarization potentiates the Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Potassium influences the Ca 2ϩ handling by depolarization of the cell membrane of smooth muscle cells in the arterial wall, resulting in vasoconstriction. This simulation of arterial tone is commonly used in other studies on arterial vasoregulation (35)(36)(37). It is unlikely that the induced state of tone will bear impact on the results of insulin-mediated vasoreactivity and PKC activation because we found that insulin-mediated vasodilation is NO dependent and insulin-mediated vasoconstriction is ET-1 dependent.…”
Section: Discussionmentioning
confidence: 80%
“…Potassium influences the Ca 2ϩ handling by depolarization of the cell membrane of smooth muscle cells in the arterial wall, resulting in vasoconstriction. This simulation of arterial tone is commonly used in other studies on arterial vasoregulation (35)(36)(37). It is unlikely that the induced state of tone will bear impact on the results of insulin-mediated vasoreactivity and PKC activation because we found that insulin-mediated vasodilation is NO dependent and insulin-mediated vasoconstriction is ET-1 dependent.…”
Section: Discussionmentioning
confidence: 80%
“…Other K + channel openers, such as levcromakalim, cromakalim, KRN2391, Ki4032, E4080 and Ki1769, have been shown to have a Ca 2+ desensitizing action in coronary arteries through membrane hyperpolarization (Okada et al 1992a(Okada et al , 1993aYokoyama et al 1995). Conversely, membrane depolarization potentiates Ca 2÷ sensitization induced by endothelin-1 in coronary artery (Okada et al 1992b). Thus, the Ca 2+ sensitivity of contractile elements in arterial smooth muscle may be partly regulated by the membrane potential (Yanagisawa and Okada 1994).…”
Section: Effect Of Krn 4884 Onmentioning
confidence: 99%
“…However, recently it has been found that in Ca 2+ -free physiological salt solution (pCa>9) containing endothelin, depolarization by high K + increases the force of contraction in canine coronary artery without any changes in [Ca 2+ ] i [33]. More recently, we demonstrated that K + evokes reversible and reproducible contractions in endothelium-denuded rat aorta bathed in Ca-free, K-rich isotonic salt solution containing EDTA [23].…”
Section: Introductionmentioning
confidence: 72%
“…K + -induced contraction in Ca-free, Mg-free medium may also be due to sensitization of the contractile elements. It has been proposed that the change of membrane potential by K + is a transducer mechanism for the alteration of myofilament Ca 2+ sensitivity in smooth muscle cells [33]. However, this seems unlikely, since it was also noted that high K + itself is unable to change the force of canine coronary artery in Ca-free, normal-Mg medium containing EGTA [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation